Kompotensi Guru PPKn dalam Membina Kepribadian Perilaku Disiplin Peserta Didik Kelas X di Sekolah SMK Negeri 8 Samarinda - Robby Hasbi; Asnar Asnar; Wingkolatin Wingkolatin; A. Hardoko; Moh Bahzar; Novita Majid (International Forum of Researchers and Lecturers, 2024)
Teacher competency is a set of mastery of abilities that must exist in teachers in order to realize their performance appropriately and effectively. Discipline is obedience to existing rules, and discipline means obeying rules, and discipline includes all matters related to discipline. The aim of this research is to describe teacher competency in developing students' disciplined behavior at SMKN 8 Samarinda school and to describe the implementation of developing students' disciplined personality at SMKN 8 Samarinda school. Types of qualitative phenomenological research. The research was conducted at SMK Negeri 8 Samarinda in December 2023-January 2024. The research subjects were one principal, two PPKN teachers and five students using observation, interview and documentation techniques. Data analysis techniques are data collection, data reduction, data presentation and data collection. The results of the research show that Teacher Competency in Developing Students' Disciplinary Behavior Personality at SMKN 8 Samarinda School, teachers have teacher competency which includes educating, guiding, teaching, training and evaluating in developing students' disciplined personality at State Vocational School 8 Samarinda. And in its implementation, PPKN teachers use several methods, including habituation, example, creating a conducive atmosphere, regulations, punishments and rewards in developing the disciplined personality of students at SMK Negeri 8 Samarinda.